2020
DOI: 10.1051/e3sconf/202016001002
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Plates: Different Materials and Processing Methods for Their Usage in Fuel Cells

Abstract: Graphite composites based bipolar plates are a preferred material for stationary PEM fuel cell applications, because they are resistant against high temperatures and corrosive conditions. This chapter gives an overview about different material configurations as well as the most important parameters and characterization methods for graphite based bipolar plates. It describes the actual generation PPS based composite materials with improved long-term stability. It introduces the most common materials and gives a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Thermoplastics in the lower right region of high temperature stability and semi‐crystallinity (i.e., PP and PE) of the pyramid are preferred for BPs in low‐temperature PEMFC (with operating temperature of 60°C –80°C [107]), while those in the upper right region of high‐temperature stability and semi‐crystallinity are suitable for BPs in high‐temperature PEMFC (with operating temperature of 120°C–180°C [108]). This is because these polymers can safely withstand the corrosive environment and provide heat deflection temperatures above the operating conditions presented by the respective type of PEMFC [109].…”
Section: Relationship Between Formulation Processing and Properties O...mentioning
confidence: 99%
See 2 more Smart Citations
“…Thermoplastics in the lower right region of high temperature stability and semi‐crystallinity (i.e., PP and PE) of the pyramid are preferred for BPs in low‐temperature PEMFC (with operating temperature of 60°C –80°C [107]), while those in the upper right region of high‐temperature stability and semi‐crystallinity are suitable for BPs in high‐temperature PEMFC (with operating temperature of 120°C–180°C [108]). This is because these polymers can safely withstand the corrosive environment and provide heat deflection temperatures above the operating conditions presented by the respective type of PEMFC [109].…”
Section: Relationship Between Formulation Processing and Properties O...mentioning
confidence: 99%
“…Classification pyramid of common plastics. PA = polyamide, PBT = polybutylene terephthalate, PET = polyethylene terephthalate, POM = polyoxymethylene, PTFE = polytetrafluoroethylene, PMMA = poly(methyl methacrylate), PS = polystyrene, ABS = acrylonitrile butadiene styrene, PBI = polybenzimidazole, TPI = thermoplastic polyimide, PES = polyether sulfone, PSU = polysulfone [109]…”
Section: Relationship Between Formulation Processing and Properties O...mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, PEMFC MI coated with carbon-based material has been reported as a cost-effective approach to improving corrosion resistance while keeping the ICR low [ 20 , 21 ]. Electrically conductive polymers (ECP) were studied as potential coating materials due to their chemical and electrochemical stability [ 22 , 23 ]. The presence of micro-defects, as a matter of the main disadvantage of ECP, can be used as migration channels for corrosive ions to penetrate to the substrate surface and passivate the interconnect, which could further increase the ICR [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%